Comparative Study of Strengthened Steel Structure Behavior Using Bracing and Shearwall - Khairullah Yusuf; Fasdarsyah Fasdarsyah; Nura Usrina; M Fauzan; Rahmi Nurahim (Department of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2023)
Multi-storey buildings are very susceptible to lateral forces, so reinforcement is needed to stiffen the building by adding a system of stiffeners to the building structure. In steel building structures, the system of stiffeners bracing and confessor shearwall can provide rigidity and strength by limiting the movement of the structure. In addition, the placement of stiffener systems in the right locations can also increase the rigidity of the building structure. This study aims to compare the effectiveness of structural behavior using a stiffener system based on the value of the fundamental period (T), the base shear force (V), the drift between stories (?x). In this research using a steel structure model that functions as an office building with a height of 10 levels, one variation of the model without stiffeners and four models with stiffeners, with two variations of the position of the stiffeners, namely in the middle and on the edge of the structure. The results of this study indicate that the addition of a stiffener system can increase the rigidity of the structure. The most effective structural model is found in the structural model with stiffeners shearwall the stiffener position in the middle which has a fundamental period value in the X and Y directions of 17.67% and 18.32% is better than the other models. For the base shear force values in the X and Y directions are 0.95% and 0.95% smaller than the other models. The deviation values between floor levels in the X and Y directions are 9.67% and 34.17% better than the other models. Meanwhile, the inefficient structural model is found in the structural model with stiffeners bracing on the edge which has a fundamental period value in the X and Y directions of 8.96% and 9.32% which is no better than the other models. For the base shear force values in the X and Y directions are 18.02% and 18.02% greater than the other models. The deviation values between floor levels in the X and Y directions are 1.69% and 13.15%, not better than the other models. So in this study it can be concluded that the stiffener system with a position in the middle is better than the position on the edge.